The Effect Of Female Leadership On Employee Performance In The Social Services Agency Of Gorontalo Province - Mowuu, Dewi Cantika Putri; Abdussamad, Juriko; Nani, Yacob Noho (Universitas Negeri Gorontalo, 2025)
Employee performance is a crucial aspect that must be taken seriously by every organization because performance reflects the organization's ability to compete and survive in a dynamic and changing environment. However, currently, the Gorontalo Provincial Social Service still shows indicators of employee performance that have not been fully achieved. This can be seen from the uneven quality of work, which is reflected in the discrepancy between employee performance and the established service standards. This research will be conducted at the Gorontalo Provincial Social Service, motivated by the continuing challenges in improving employee performance at the Gorontalo Provincial Social Service, which has implications for the optimization of public services in the field of social welfare. Based on the theory proposed by Sedarmayanti, there are five main performance indicators that can be used as a basis for identifying problems in this agency. The purpose of this study is to determine the influence of female leadership on employee performance at the Gorontalo Provincial Social Service. The research method used is quantitative research, through which the problems to be studied in each variable can be seen. The population of the study on “The Influence of Female Leadership on Employee Performance at the Gorontalo Provincial Social Service” was all 122 employees at the Gorontalo Provincial Social Service. The data was collected from questionnaires distributed to 30 employees who were the subjects of the study. The results of this study show that female leadership has a positive and significant effect on employee performance, with female leadership accounting for 51.2% of the effect and the remaining 48.8% being influenced by other factors not examined in this study at the Gorontalo Provincial Social Services Agency.